Effects of steel fibres on fresh and hardened properties of cement concrete - Ali, Saqib; Kumar, Haresh; Rizvi, Samar Hussain; Raza, Muhammad Saleem; Ansari, Jawaid Kamal (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Concrete possesses distinct features that make it widely acceptable for use across the globe; however, along with its obvious benefits, it has numerous drawbacks i.e., it is brittle in nature and its production causes an adverse impact on the environment. To counter such problems, researchers around the world have introduced sustainable measures. Fibre addition is foremost among these solutions in that it prevents crack propagation and increases the overall strength of concrete.
Keywords: cement concrete; steel fibre; compressive strength; tensile strength; workability; beton cementowy; włókna stalowe; wytrzymałość na ściskanie; wytrzymałość na rozciąganie; urabialność